Preparation method of aluminum-based lithium extraction adsorbent, aluminum-based lithium extraction adsorbent and application of aluminum-based lithium extraction adsorbent

Through a preparation method of aluminum-based lithium-extracting adsorbent, the problems of complex and high cost in traditional methods are solved, and an efficient, low-cost and environmentally friendly lithium extraction process is achieved, which significantly improves the lithium extraction efficiency.

CN119425614APending Publication Date: 2025-02-14BEIJING HUATEYUAN TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411826896.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The preparation of traditional lithium-aluminum layered double hydroxide adsorbents has problems such as complex preparation process, low raw material utilization rate, large energy consumption, high production costs and environmental pollution.

Method used

Using an aluminum-based lithium-extracting adsorbent preparation method, by mixing the lithium compound, aluminum compound, pore-generating agent and dispersing agent evenly, adding solvent to disperse and grinding, then performing first drying and steam roasting, and finally pelletizing The glue is mixed and molded to obtain an aluminum-based lithium-extracting adsorbent.

Benefits of technology

This method improves the specific surface area and porosity of the adsorbent, optimizes the performance of the adsorbent, reduces the difficulty and cost of operation, is suitable for industrial large-scale production, and significantly improves the extraction efficiency of lithium.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425614A_ABST
    Figure CN119425614A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an aluminum-based lithium extraction adsorbent, the aluminum-based lithium extraction adsorbent and application of the aluminum-based lithium extraction adsorbent, and particularly relates to the technical field of lithium ion sieves. The preparation method of the aluminum-based lithium extraction adsorbent comprises the following steps: A, uniformly mixing a lithium compound, an aluminum compound, a pore-foaming agent and a dispersing agent, adding a solvent, dispersing and grinding to obtain slurry; b, the slurry is subjected to first drying and then placed in a tubular furnace, water vapor is introduced for roasting, and precursor powder is obtained; and C, mixing the precursor powder with granulation glue, extruding into strips, drying for the second time, and crushing to obtain the aluminum-based lithium extraction adsorbent. The preparation method is continuous in process and mild in condition, high-efficiency conversion of the raw materials can be realized without a complicated process, excessive loss of the raw materials and generation of pollutants are avoided, the operation difficulty and cost are greatly reduced, and industrial large-scale production is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion sieves, and in particular to a preparation method of an aluminum-based lithium extraction adsorbent, the aluminum-based lithium extraction adsorbent and applications thereof. Background Art

[0002] In the field of lithium extraction from salt lakes, adsorption has become an important technology due to its adaptability, environmental friendliness and sustainability. Adsorbents in lithium recovery are mainly divided into three types: lithium manganese oxide, titanate and lithium aluminum layered double hydroxide. In contrast, lithium aluminum layered double hydroxide is highly selective for lithium ions and can effectively identify and adsorb lithium ions in complex brine environments while eliminating interference from other coexisting ions. It also maintains stable adsorption performance over a wide range of temperatures and pH values ​​and is not easily affected by environmental factors. Therefore, aluminum-based lithium extraction adsorbents have played an important role in the process of lithium extraction from salt lakes due to their excellent performance characteristics, and have become the most widely used type of adsorbent product.

[0003] The preparation of traditional lithium aluminum layered double hydroxide adsorbents usually involves coprecipitation, sol-gel method, ion exchange and other technologies. These methods are quite mature on a laboratory scale, but in industrial applications, there are problems such as complex preparation process, low raw material utilization, high energy consumption, high production cost and environmental pollution. Therefore, the development of new lithium extraction adsorbent preparation technology to achieve efficient, low-cost and environmentally friendly lithium extraction process is an important direction of current research.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] One of the purposes of the present invention is to provide a method for preparing an aluminum-based lithium extraction adsorbent, aiming to solve at least one of the above-mentioned technical problems in the prior art.

[0006] A second object of the present invention is to provide an aluminum-based lithium extraction adsorbent.

[0007] The third object of the present invention is to provide an application of an aluminum-based lithium extraction adsorbent.

[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0009] The first aspect of the present invention provides a method for preparing an aluminum-based lithium extraction adsorbent, comprising the following steps:

[0010] A. mixing a lithium compound, an aluminum compound, a porogen and a dispersant uniformly, adding a solvent for dispersion and grinding to obtain a slurry;

[0011] B. drying the slurry for the first time, and then placing it in a tube furnace and introducing water vapor for calcining to obtain a precursor powder;

[0012] C. The precursor powder is mixed with granulated rubber, extruded into strips, dried for a second time, and crushed to obtain the aluminum-based lithium extraction adsorbent.

[0013] Furthermore, the molar ratio of the aluminum in the aluminum compound to the lithium in the lithium compound is 2:0.2 to 1.5, preferably 2:0.5 to 1.5.

[0014] Preferably, the aluminum compound includes at least one of aluminum oxide, aluminum sulfide, aluminum hydroxide, gibbsite, aluminum chloride, aluminum sulfate, aluminum nitrate, aluminum silicate and alum.

[0015] Preferably, the lithium compound includes at least one of lithium chloride, lithium carbonate, lithium sulfate, lithium nitrate and lithium hydroxide.

[0016] Furthermore, the porogen includes at least one of sodium chloride, sodium carbonate, sodium sulfate, ammonium bicarbonate, bentonite and sucrose.

[0017] Preferably, the added amount of the porogen is 8-20% of the total amount of the lithium compound and the aluminum compound.

[0018] Preferably, the dispersant includes at least one of sodium citrate, sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate and sodium silicate.

[0019] Preferably, the added amount of the dispersant is 5-12% of the total amount of the lithium compound and the aluminum compound.

[0020] Preferably, the solvent comprises ethanol and / or water.

[0021] Furthermore, the first drying is carried out at a temperature of 60 to 150° C. and for a time of 2 to 6 hours.

[0022] Preferably, the grinding speed is 500-1000 rpm and the grinding time is 1-3 hours.

[0023] Preferably, the calcination temperature is 150-400° C. and the calcination time is 3-8 hours.

[0024] Preferably, the flow rate of the water vapor is 500-5000 mL / min.

[0025] Furthermore, the granulated rubber includes at least one of PVC, PVP, PAM, PAN, PES, PVDF, gelatin and gum arabic.

[0026] Preferably, the amount of the granulation rubber is 1 to 4 times the mass of the precursor powder.

[0027] Preferably, the second drying is carried out at a temperature of 60 to 200° C. and for a time of 4 to 24 hours.

[0028] Preferably, the particle size of the aluminum-based lithium extraction adsorbent is 1 to 3 mm.

[0029] The second aspect of the present invention provides an aluminum-based lithium extraction adsorbent, which is prepared by the preparation method described in the first aspect.

[0030] The aluminum-based lithium extraction adsorbent is Li / Al-LDH, and the chemical formula is LiCl·2Al(OH)3·nH2O.

[0031] Among them, n is a value of 1 to 3.

[0032] The third aspect of the present invention provides the use of the aluminum-based lithium extraction adsorbent described in the invention in lithium extraction from salt lakes.

[0033] Furthermore, the method for using the aluminum-based lithium extraction adsorbent is: filling the aluminum-based lithium extraction adsorbent in a reaction column, and passing pure water for activation; after activation, passing brine into the reaction column for adsorption, after completion, using pure water as a feed liquid for water washing and analysis to obtain an analysis liquid, and finally concentrating and separating the lithium in the analysis liquid to obtain a lithium compound.

[0034] Furthermore, the activation time is 2 to 6 hours.

[0035] Preferably, during the activation process, the flow rate of pure water is 10 to 20 BV / h.

[0036] Furthermore, the feed flow rate of the brine is 3 to 10 BV / h.

[0037] Preferably, the adsorption time is 4 to 10 hours.

[0038] Preferably, during the water washing process, the flow rate of pure water is 5 to 20 BV / h.

[0039] Preferably, the analysis time is 1 to 3 hours.

[0040] Compared with the prior art, the present invention has at least the following beneficial effects:

[0041] The preparation method of the aluminum-based lithium-extraction adsorbent provided by the present invention first increases the specific surface area of ​​the powder by grinding, promotes contact between particles, accelerates the reaction rate, and regulates the particle size distribution and morphology of the material, thereby optimizing the performance of the adsorbent; grinding not only increases the specific surface area and porosity of the adsorbent, but also ensures the uniform distribution of the pore structure, further improving the mass transfer efficiency. During the steam roasting process, the water vapor reacts chemically with the surface of the material, removes some substances, increases the porosity and specific surface area of ​​the material, and protects the structure to be stable and not easy to collapse, ensuring that the material completes crystallization while protecting the crystallization water structure between the material layers to maintain structural stability. The preparation method has a continuous process and mild conditions. It can achieve efficient conversion of raw materials without complex process, avoids excessive loss of raw materials and generation of pollutants, greatly reduces the difficulty and cost of operation, and is conducive to industrial large-scale production.

[0042] The aluminum-based lithium extraction adsorbent provided by the present invention, in view of the advantages of the above-mentioned preparation method, makes the prepared adsorbent have a larger specific surface area, developed pores, more and more uniformly distributed pore structures, and higher mass transfer efficiency. At the same time, the adsorbent has a high lithium-aluminum ratio, which improves the stability of the adsorbent structure. In addition, the water content of the interlayer structure of the adsorbent is increased, the interlayer structure becomes larger, and the adsorbent capacity is improved. The capacity of the adsorbent can reach 2.3-3.5 mg / g, and it has better selectivity for Na, K, Ca, and Mg ions.

[0043] The application of the aluminum-based lithium extraction adsorbent provided by the present invention provides an adsorbent with better performance for lithium extraction from salt lakes, reduces the use cost of the adsorbent, and significantly improves the extraction efficiency of lithium through its high adsorption capacity and high selectivity. The application of this adsorbent makes the extraction of lithium from salt lake brine more economical and environmentally friendly, and also enhances the sustainability of the entire lithium extraction process. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0045] Figure 1 XRD pattern provided for characterization example 1. DETAILED DESCRIPTION

[0046] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0047] Hereinafter, the terms "including", "having" and their cognates, which may be used in various embodiments of the present invention, are intended only to indicate specific features, numbers, steps, operations, elements, components or combinations of the foregoing items, and should not be understood as first excluding the existence of one or more other features, numbers, steps, operations, elements, components or combinations of the foregoing items or adding the possibility of one or more features, numbers, steps, operations, elements, components or combinations of the foregoing items.

[0048] The first aspect of the present invention provides a method for preparing an aluminum-based lithium extraction adsorbent, comprising the following steps:

[0049] A. mixing a lithium compound, an aluminum compound, a porogen and a dispersant uniformly, adding a solvent for dispersion and grinding to obtain a slurry;

[0050] B. drying the slurry for the first time, and then placing it in a tube furnace and introducing water vapor for calcining to obtain a precursor powder;

[0051] C. The precursor powder is mixed with granulated rubber, extruded into strips, dried for a second time, and crushed to obtain the aluminum-based lithium extraction adsorbent.

[0052] The preparation method of the aluminum-based lithium-extraction adsorbent provided by the present invention first increases the specific surface area of ​​the powder by grinding, promotes contact between particles, accelerates the reaction rate, and regulates the particle size distribution and morphology of the material, thereby optimizing the performance of the adsorbent; grinding not only increases the specific surface area and porosity of the adsorbent, but also ensures the uniform distribution of the pore structure, further improving the mass transfer efficiency. During the steam roasting process, the water vapor reacts chemically with the surface of the material, removes some substances, increases the porosity and specific surface area of ​​the material, and protects the structure to be stable and not easy to collapse, ensuring that the material completes crystallization while protecting the crystallization water structure between the material layers to maintain structural stability. The preparation method has a continuous process and mild conditions. It can achieve efficient conversion of raw materials without complex process, avoids excessive loss of raw materials and generation of pollutants, greatly reduces the difficulty and cost of operation, and is conducive to industrial large-scale production.

[0053] The porogen occupies a specific volume during the adsorbent forming stage, and then gradually dissolves and separates from the adsorbent structure during the steam roasting stage due to its water-soluble properties. This process forms a pore structure inside the adsorbent, which significantly increases the specific surface area of ​​the adsorbent. These newly added pores provide more active sites for the adsorption process, thereby improving mass transfer efficiency and optimizing adsorption performance.

[0054] Dispersants help to improve the uniform dispersion of aluminum compounds, lithium compounds, porogens and other components in the solvent, prevent particle agglomeration, reduce slurry viscosity, improve its fluidity, and also increase the rate and efficiency of chemical reactions, enhance the stability of slurries, and ensure that no sedimentation or stratification occurs during storage and handling. In addition, dispersants optimize the pore structure of adsorbents by controlling the formation of pores, thereby improving the adsorption capacity, selectivity and cycle stability of adsorbents. Ultimately, the use of dispersants helps to improve the utilization of raw materials, reduce losses in the production process, and reduce overall production costs, thereby optimizing cost-effectiveness while improving adsorbent performance.

[0055] Furthermore, the molar ratio of the aluminum in the aluminum compound to the lithium in the lithium compound is 2:0.2 to 1.5, preferably 2:0.5 to 1.5.

[0056] Within the above molar ratio range, it is helpful to form an aluminum-lithium layered structure with optimal adsorption performance, which can provide more active sites, thereby enhancing the adsorption capacity of lithium ions. At the same time, the structural stability of the adsorbent is ensured to avoid structural instability caused by improper ratios or interlayer collapse during the adsorption process. At the same time, cost-effectiveness is considered, the amount of raw materials used is optimized, the flexibility of the synthesis process is provided, and the adsorbent is adapted to different chemical environments to maintain efficient adsorption performance.

[0057] Typically, but not limiting, the molar ratio of aluminum to lithium can be 2:0.2, 2:0.3, 2:0.4, 2:0.5, 2:0.6, 2:0.7, 2:0.8, 2:0.9, 2:1.0, 2:1.1, 2:1.2, 2:1.3, 2:1.4 or 2:1.5, or any value in the range of 2:0.2 to 1.5. Preferably, the molar ratio can be 2:0.5, 2:0.6, 2:0.7, 2:0.8, 2:0.9, 2:1.0, 2:1.1, 2:1.2, 2:1.3, 2:1.4 or 2:1.5, or any value in the range of 2:0.5 to 1.5.

[0058] Preferably, the aluminum compound includes at least one of aluminum oxide, aluminum sulfide, aluminum hydroxide, gibbsite, aluminum chloride, aluminum sulfate, aluminum nitrate, aluminum silicate and alum.

[0059] Preferably, the lithium compound includes at least one of lithium chloride, lithium carbonate, lithium sulfate, lithium nitrate and lithium hydroxide.

[0060] Furthermore, the porogen includes at least one of sodium chloride, sodium carbonate, sodium sulfate, ammonium bicarbonate, bentonite and sucrose.

[0061] Preferably, the added amount of the porogen is 8-20% of the total amount of the lithium compound and the aluminum compound.

[0062] Typically but not limiting, the amount of the porogen added can be 8%, 10%, 12%, 14%, 16%, 18% or 20% of the total amount of the lithium compound and the aluminum compound, or any value within the range of 8% to 20%.

[0063] Preferably, the dispersant includes at least one of sodium citrate, sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate and sodium silicate.

[0064] Preferably, the added amount of the dispersant is 5-12% of the total amount of the lithium compound and the aluminum compound.

[0065] Typically but not limiting, the amount of the dispersant added can be 5%, 6%, 7%, 8%, 9%, 10%, 11% or 12% of the total amount of the lithium compound and the aluminum compound, or any value within the range of 5% to 12%.

[0066] Preferably, the solvent comprises ethanol and / or water.

[0067] Furthermore, the first drying is carried out at a temperature of 60 to 150° C. and for a time of 2 to 6 hours.

[0068] Typically but not limiting, in the first drying process, the temperature can be set to 60, 70, 80, 90, 100, 110, 120, 130, 140 or 150, or any value in the range of 60 to 150; the drying time can be 2 hours, 3 hours, 4 hours, 5 hours or 6 hours, or any value in the range of 2 hours to 6 hours.

[0069] Preferably, the grinding speed is 500-1000 rpm and the grinding time is 1-3 hours.

[0070] Typically but not limiting, during the grinding process, the rotation speed can be set to 500rpm, 600rpm, 700rpm, 800rpm, 900rpm or 1000rpm, or any value within the range of 500rpm to 1000rpm; the grinding time can be 1 hour, 2 hours or 3 hours, or any value within the range of 1 hour to 3 hours.

[0071] Preferably, the calcination temperature is 150-400° C. and the calcination time is 3-8 hours.

[0072] Typically but not limiting, during the calcination process, the temperature can be set to 150, 200, 250, 300, 350 or 400, or any value within the range of 150 to 400; the calcination time can be 3 hours, 4 hours, 5 hours, 6 hours, 7 hours or 8 hours, or any value within the range of 3 hours to 8 hours.

[0073] Preferably, the flow rate of the water vapor is 500-5000 mL / min.

[0074] Typically but not limiting, the flow rate of water vapor introduced can be 500mL / min, 1000mL / min, 1500mL / min, 2000mL / min, 2500mL / min, 3000mL / min, 3500mL / min, 4000mL / min or 5000mL / min, or it can be any value within the range of 500mL / min to 5000mL / min.

[0075] Steam roasting utilizes the thermal effect and chemical reaction characteristics of water vapor to promote the crystallization of materials and the formation of pore structures at lower temperatures, thereby increasing the specific surface area and porosity of the materials. Since water vapor is non-toxic and harmless, this process is not only highly safe and does not produce toxic or harmful byproducts, but is also environmentally friendly and reduces potential pollution to air and water quality. In addition, during the steam roasting process, the interaction between water molecules and the adsorbent surface helps to remove some substances and further optimize the pore characteristics of the material, while protecting the structural stability and preventing collapse at high temperatures. This roasting method has low energy consumption, simple operation, and easy control.

[0076] Furthermore, the granulated rubber includes at least one of PVC, PVP, PAM, PAN, PES, PVDF, gelatin and gum arabic.

[0077] Preferably, the amount of the granulation rubber is 1 to 4 times the mass of the precursor powder.

[0078] Typically but not limiting, the amount of the granulation rubber can be 1 times, 1.5 times, 2 times, 2.5 times, 3 times or 4 times the mass of the precursor powder, or any value within the range of 1 to 4 times.

[0079] Preferably, the second drying is carried out at a temperature of 60 to 200° C. and for a time of 4 to 24 hours.

[0080] Typically but not limiting, in the second drying process, the temperature can be set to 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190 or 200, or any value in the range of 60 to 200; the drying time can be 4 hours, 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours or 24 hours, or any value in the range of 4 hours to 24 hours.

[0081] Preferably, the particle size of the aluminum-based lithium extraction adsorbent is 1 to 3 mm.

[0082] The second aspect of the present invention provides an aluminum-based lithium extraction adsorbent, which is prepared by the preparation method described in the first aspect.

[0083] The aluminum-based lithium extraction adsorbent is Li / Al-LDH, and the chemical formula is LiCl·2Al(OH)3·nH2O.

[0084] Here, n ranges from 1 to 3.

[0085] The aluminum-based lithium extraction adsorbent provided by the present invention, in view of the advantages of the above-mentioned preparation method, makes the prepared adsorbent have a larger specific surface area, developed pores, more and more uniformly distributed pore structures, and higher mass transfer efficiency. At the same time, the adsorbent has a high lithium-aluminum ratio, which improves the stability of the adsorbent structure. In addition, the water content of the interlayer structure of the adsorbent is increased, the interlayer structure becomes larger, and the adsorbent capacity is improved. The capacity of the adsorbent can reach 2.3-3.5 mg / g, and it has better selectivity for Na, K, Ca, and Mg ions.

[0086] The third aspect of the present invention provides the use of the aluminum-based lithium extraction adsorbent described in the invention in lithium extraction from salt lakes.

[0087] The application of the aluminum-based lithium extraction adsorbent provided by the present invention provides an adsorbent with better performance for lithium extraction from salt lakes, reduces the use cost of the adsorbent, and significantly improves the extraction efficiency of lithium through its high adsorption capacity and high selectivity. The application of this adsorbent makes the extraction of lithium from salt lake brine more economical and environmentally friendly, and also enhances the sustainability of the entire lithium extraction process.

[0088] Furthermore, the method for using the aluminum-based lithium extraction adsorbent is: filling the aluminum-based lithium extraction adsorbent in a reaction column, and passing pure water for activation; after activation, passing brine into the reaction column for adsorption, after completion, using pure water as a feed liquid for water washing and analysis to obtain an analysis liquid, and finally concentrating and separating the lithium in the analysis liquid to obtain a lithium compound.

[0089] The purpose of activation of aluminum-based lithium-extraction adsorbents during use is to change the chemical properties and structure of the adsorbent surface, thereby optimizing its adsorption sites to enhance the adsorption capacity of lithium ions. This includes increasing the number of adsorption sites, improving their distribution, and adjusting their chemical properties to make them more conducive to interaction with lithium ions. The activation process can also help remove pollutants and impurities on the adsorbent surface, which may interfere with the adsorption process of lithium ions. Through cleaning and regeneration treatments, the cleanliness of the adsorbent can be restored and its adsorption efficiency can be improved. The activation process helps to restore and improve the performance of the adsorbent, optimize the pore structure to adapt to specific adsorption requirements, and improve the adsorption efficiency.

[0090] Furthermore, the activation time is 2 to 6 hours.

[0091] Typically but not limiting, the activation time can be set to 2 hours, 3 hours, 4 hours, 5 hours or 6 hours, or any value within the range of 2 hours to 6 hours.

[0092] Preferably, during the activation process, the flow rate of pure water is 10 to 20 BV / h.

[0093] Typically but not limiting, during the activation process, the flow rate of pure water can be 10BV / h, 12BV / h, 14BV / h, 16BV / h, 18BV / h or 20BV / h, or any value within the range of 10BV / h to 20BV / h.

[0094] Furthermore, the feed flow rate of the brine is 3 to 10 BV / h.

[0095] Typically but not limiting, the feed flow rate of the brine can be 3BV / h, 4BV / h, 5BV / h, 6BV / h, 7BV / h, 8BV / h, 9BV / h or 10BV / h, or any value within the range of 3BV / h to 10BV / h.

[0096] Preferably, the adsorption time is 4 to 10 hours.

[0097] Typically but not limiting, during the adsorption process, the time can be set to 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours, or any value within the range of 4 hours to 10 hours.

[0098] Preferably, during the water washing process, the flow rate of pure water is 5 to 20 BV / h.

[0099] Typically but not restrictively, during the water washing process, the flow rate of pure water can be 5BV / h, 7BV / h, 10BV / h, 13BV / h, 15BV / h, 17BV / h, 19BV / h or 20BV / h, or it can be any value within the range of 5BV / h to 20BV / h.

[0100] Preferably, the analysis time is 1 to 3 hours.

[0101] Typically but not limiting, during the analysis process, the time can be set to 1 hour, 1.5 hours, 2 hours or 3 hours, or any value within the range of 1 hour to 3 hours.

[0102] The present invention is further described below by specific examples and comparative examples, but it should be understood that these examples are only used for more detailed description and should not be understood as limiting the present invention in any form. The raw materials used in the examples and comparative examples of the present invention, if no specific conditions are specified, are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0103] Example 1

[0104] This embodiment provides an aluminum-based lithium extraction adsorbent, and the preparation steps are as follows:

[0105] 1. Mix and grind 102 g of alumina powder, 42.5 g of lithium chloride powder, 30 g of sodium chloride and 15 g of sodium tripolyphosphate powder, and add a small amount of water dropwise to obtain a slurry.

[0106] 2. The slurry was placed in a 60°C oven and dried for 4 hours to obtain a mixed powder. The mixed powder was then calcined in a tube furnace with 250°C steam for 4 hours at a steam concentration of 0.5 L / min to obtain a precursor powder.

[0107] 3. The above precursor powder was fully mixed with 50g PVP and 10g PVC and formed into a strip solid using an extruder. The strip solid was placed in an oven and cured at 80°C for 6 hours, and then crushed into particles to obtain aluminum adsorbent particles.

[0108] Example 2

[0109] This embodiment provides an aluminum-based lithium extraction adsorbent, and the preparation steps are as follows:

[0110] 1. Mix and grind 400 g aluminum chloride powder, 109.9 g lithium sulfate powder, 50 g bentonite and 30 g sodium citrate, and add a small amount of water dropwise to obtain a slurry.

[0111] 2. The slurry was placed in an oven at 80°C for 2 hours to obtain a mixed powder. The mixed powder was then calcined in a tube furnace at 400°C for 6 hours with a water vapor concentration of 1 L / min to obtain a precursor powder.

[0112] 3. The above precursor powder and 100g PVDF were fully stirred and mixed, and then formed into a strip solid using an extruder. The strip solid was placed in an oven and cured at 100°C for 2h, and then crushed into particles to obtain aluminum-based adsorbent particles.

[0113] Example 3

[0114] This embodiment provides an aluminum-based lithium extraction adsorbent, and the preparation steps are as follows:

[0115] 1. Mix and grind 156 g aluminum hydroxide powder, 73.9 g lithium carbonate powder, 18.4 g sodium carbonate and 11.5 g sodium silicate powder, and add a small amount of water dropwise to obtain a slurry.

[0116] 2. The slurry was placed in an oven at 100°C for 3 hours to obtain a mixed powder. The mixed powder was then calcined in a tube furnace at 300°C for 6 hours with a water vapor concentration of 1 L / min to obtain a precursor powder.

[0117] 3. The above precursor powder was fully stirred and mixed with 60g gelatin and 15g PVDF, and then formed into a strip solid using an extruder. The strip solid was placed in an oven and cured at 100°C for 5h, and then crushed into particles to obtain aluminum-based adsorbent particles.

[0118] Example 4

[0119] This embodiment provides an aluminum-based lithium extraction adsorbent. The difference from Example 1 is that the amount of lithium chloride used is 21.3 g, and the remaining raw materials and preparation methods are the same as those in Example 1, which will not be repeated here.

[0120] Example 5

[0121] This embodiment provides an aluminum-based lithium extraction adsorbent. The difference from Example 1 is that the amount of lithium chloride used is 63.9 g, and the remaining raw materials and preparation methods are the same as those in Example 1, which will not be repeated here.

[0122] Example 6

[0123] This embodiment provides an aluminum-based lithium extraction adsorbent. The difference from Example 1 is that the amount of sodium chloride used is 11.56 g, and the remaining raw materials and preparation methods are the same as those in Example 1, which will not be repeated here.

[0124] Example 7

[0125] This embodiment provides an aluminum-based lithium extraction adsorbent. The difference from Example 1 is that the amount of sodium chloride used is 28.9 g, and the remaining raw materials and preparation methods are the same as those in Example 1, which will not be repeated here.

[0126] Example 8

[0127] This embodiment provides an aluminum-based lithium extraction adsorbent. The difference from Example 1 is that the amount of sodium tripolyphosphate powder used is 7.2 g, and the remaining raw materials and preparation methods are the same as those in Example 1, which will not be repeated here.

[0128] Example 9

[0129] This embodiment provides an aluminum-based lithium extraction adsorbent. The difference from Example 1 is that the amount of sodium tripolyphosphate powder used is 17.34 g, and the remaining raw materials and preparation methods are the same as those in Example 1, which will not be repeated here.

[0130] Comparative Example 1

[0131] This comparative example provides an aluminum-based lithium extraction adsorbent. The difference from Example 1 is that sodium chloride is not added, and the remaining raw materials and preparation methods are the same as those in Example 1, which will not be repeated here.

[0132] Comparative Example 2

[0133] This comparative example provides an aluminum-based lithium extraction adsorbent. The difference from Example 1 is that sodium tripolyphosphate powder is not added, and the remaining raw materials and preparation methods are the same as those in Example 1, which will not be repeated here.

[0134] Comparative Example 3

[0135] This comparative example provides an aluminum-based lithium extraction adsorbent. The difference from Example 1 is that the steam roasting is changed to ordinary roasting. The remaining raw materials and preparation methods are the same as those in Example 1 and are not described again.

[0136] Comparative Example 4

[0137] This comparative example provides an aluminum-based lithium extraction adsorbent. The difference from Example 2 is that the steam roasting is changed to ordinary roasting. The remaining raw materials and preparation methods are the same as those in Example 2 and will not be repeated here.

[0138] Characterization Example 1

[0139] XRD was performed on the material obtained in Example 1, and the obtained picture was as follows Figure 1 As shown. Figure 1 It can be seen that the prepared adsorbent has a more obvious peak belonging to lithium aluminum hydrotalcite LiCl·2Al(OH)3·nH2O, and at the same time, some inorganic salts are retained to ensure that the metal ions in the main plate layer are not deintercalated in the solution and humid environment to maintain the stability of the adsorbent structure.

[0140] Results

[0141] The contents of lithium and aluminum in the adsorbents obtained in the examples and comparative examples were measured, and the results are shown in Table 1 below.

[0142] Table 1

[0143] Li / (mg / g) Al / (mg / g) Example 1 37 284 Example 2 24 137 Example 3 54 200 Example 4 20 321 Example 5 50 256 Example 6 41 316 Example 7 37 286 Example 8 38 297 Example 9 36 281 Comparative Example 1 44 338 Comparative Example 2 40 309 Comparative Example 3 37 284 Comparative Example 4 24 137

[0144] Test Case

[0145] The adsorbents obtained in the examples and comparative examples were tested for adsorption capacity.

[0146] The ingredients of the prepared brine are shown in Table 2 below.

[0147] Table 2

[0148] ion <![CDATA[Mg 2+ ]]> <![CDATA[Li + ]]> <![CDATA[B 3+ ]]> <![CDATA[Ca 2+ ]]> <![CDATA[K + ]]> <![CDATA[Na + ]]> <![CDATA[SO4 2- ]]> <![CDATA[Cl - ]]> Concentration (ppm) 60000 200 560 7000 2000 3000 900 300000

[0149] 1. The adsorbent particles obtained in the examples and comparative examples were loaded into a 50 mL packing column. Pure water was fed into the reaction column at a feed rate of 10 BV / h at room temperature, and the column was operated in a flow-through mode for 4 hours. The liquid in the column was drained and collected together.

[0150] 2. Prepare brine as feed liquid, keep the temperature at room temperature, and use peristaltic pump to feed into the reaction column at a feed flow rate of 3BV / h. Continue feeding for 10 hours, drain the feed liquid in the organic adsorption column, collect the discharge liquid, and use ICP to test the Li concentration, which are recorded as C 1(Li) .

[0151] 3. Drain the adsorption tail liquid in the adsorption column during the adsorption stage. Use pure water as the feed liquid and flush the packing at a feed flow rate of 5BV / h for 10 minutes. After flushing, drain the pure water in the adsorption column. Finally, use pure water as the analytical liquid feed, and feed it into the reaction column at a feed flow rate of 5BV / h at room temperature. The analytical time is 3h.

[0152] 4. Drain the analytical solution in the adsorption column, collect the circulating water, and use ICP to detect the concentrations of Li, Na, K, Ca, and Mg, and record them as C 3(Li) , C 3(Na) , C 3(K) , C 3(Ca) , C 3(Mg) , calculate Li / Na, Li / K, Li / Ca, and Li / Mg.

[0153] 5. After completion, rinse 50 mL of the liquid after the experiment in the adsorption column with pure water and spread it on a small-pore sieve, put it in an oven at 40 (±1), dry it for 8 hours, cool it to room temperature in the dryer, weigh it, record it in g, and calculate the Li resolution rate.

[0154] The obtained data are recorded in Table 3.

[0155] Table 3

[0156]

[0157]

[0158] It can be seen from Table 3 that dispersants and porogens can make the material dispersed evenly, promote the formation of pores in the material, and promote the formation of the pore structure of the material through steam roasting, thereby increasing the specific surface area of ​​the material and increasing the adsorption capacity and selectivity of the material.

[0159] Finally, it should be noted that the above-described embodiments are only specific implementations of the present invention, which are used to illustrate the technical solutions of the present invention, rather than to limit them. The protection scope of the present invention is not limited thereto. Although the present invention is described in detail with reference to the above-described embodiments, ordinary technicians in the field should understand that any technician familiar with the technical field can still modify the technical solutions recorded in the above-described embodiments within the technical scope disclosed by the present invention, or can easily think of changes, or make equivalent replacements for some of the technical features therein; and these modifications, changes or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A method for preparing an aluminum-based lithium-extraction adsorbent, characterized in that: The following steps are involved: A. mixing a lithium compound, an aluminum compound, a porogen and a dispersant uniformly, adding a solvent for dispersion and grinding to obtain a slurry; B. drying the slurry for the first time, and then placing it in a tube furnace and introducing water vapor for calcining to obtain a precursor powder; C. The precursor powder is mixed with granulated rubber, extruded into strips, dried for a second time, and crushed to obtain the aluminum-based lithium extraction adsorbent.

2. The preparation method according to claim 1, characterized in that: The molar ratio of aluminum in the aluminum compound to lithium in the lithium compound is 2:0.2 to 1.5, preferably 2:0.5 to 1.5; Preferably, the aluminum compound comprises at least one of aluminum oxide, aluminum sulfide, aluminum hydroxide, gibbsite, aluminum chloride, aluminum sulfate, aluminum nitrate, aluminum silicate and alum; Preferably, the lithium compound includes at least one of lithium chloride, lithium carbonate, lithium sulfate, lithium nitrate and lithium hydroxide.

3. The preparation method according to claim 1, characterized in that: The porogen includes at least one of sodium chloride, sodium carbonate, sodium sulfate, ammonium bicarbonate, bentonite and sucrose; Preferably, the amount of the porogen added is 8-20% of the total amount of the lithium compound and the aluminum compound; Preferably, the dispersant includes at least one of sodium citrate, sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate and sodium silicate; Preferably, the amount of the dispersant added is 5 to 12% of the total amount of the lithium compound and the aluminum compound; Preferably, the solvent comprises ethanol and / or water.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The first drying is carried out at a temperature of 60 to 150° C. and for a time of 2 to 6 hours; Preferably, the grinding speed is 500-1000 rpm, and the grinding time is 1-3 hours; Preferably, the calcination temperature is 150-400°C and the calcination time is 3-8h; Preferably, the flow rate of the water vapor is 500-5000 mL / min.

5. The preparation method according to any one of claims 1 to 3, characterized in that: The granulated rubber includes at least one of PVC, PVP, PAM, PAN, PES, PVDF, gelatin and gum arabic; Preferably, the amount of the granulation rubber is 1 to 4 times the mass of the precursor powder; Preferably, the second drying temperature is 60 to 200°C and the time is 4 to 24 hours; Preferably, the particle size of the aluminum-based lithium extraction adsorbent is 1 to 3 mm.

6. An aluminum-based lithium extraction adsorbent, characterized in that: Prepared by the preparation method according to any one of claims 1 to 5; The aluminum-based lithium extraction adsorbent is Li / Al-LDH, and its chemical formula is LiCl·2Al(OH)3·nH2O; Among them, n is a value of 1 to 3.

7. Use of the aluminum-based lithium extraction adsorbent according to claim 6 in extracting lithium from salt lakes.

8. The use according to claim 7, characterized in that: The method for using the aluminum-based lithium extraction adsorbent is as follows: the aluminum-based lithium extraction adsorbent is filled in a reaction column, and pure water is introduced for activation; after activation, brine is introduced into the reaction column for adsorption, and after completion, pure water is used as a feed liquid for washing and analysis to obtain an analysis liquid, and finally the lithium in the analysis liquid is concentrated and separated to obtain a lithium compound.

9. The use according to claim 8, characterized in that: The activation time is 2 to 6 hours; Preferably, during the activation process, the flow rate of pure water is 10 to 20 BV / h.

10. The use according to claim 8, characterized in that: The feed flow rate of the brine is 3 to 10 BV / h; Preferably, the adsorption time is 4 to 10 hours; Preferably, during the water washing process, the flow rate of pure water is 5 to 20 BV / h; Preferably, the analysis time is 1 to 3 hours.